Biliary Access During Endoscopic Retrograde Cholangiopancreatography - David L Carr-Locke (Canadian Journal of Gastroenterology)
Several techniques have been developed to facilitate cannulation of the papilla during endoscopic retrograde cholangiopancreatography (ERCP). The position of the endoscope should generally provide a 'straight' route to the papilla, and the efforts should be directed at shortening the intraduodenal portion of the bile duct. If a guidewire is used, one should be chosen that possesses suitable tip and shaft characteristics, including flexibility, strength, low friction and trackability, but no one device is likely to be suitable for all purposes. The development of guidewires composed of nitinol has revolutionized endoscopic practice. Access papillotomy ('pre-cut') can be employed as an alternative to (or in addition to) insertion of a guidewire when cannulation of the major papilla has been unsuccessful. The same techniques may be used to allow deep cannulation of the bile or pancreatic duct after ductography, when fluoroscopy can also be used. The 'needle-knife', which must be used carefully because it cuts with even slight tissue contact, is moved in the expected direction of the intramural bile (or pancreatic) duct to gain direct access into the duct. Access papillotomy is a valuable procedure in difficult cases, but is associated with greater risks than standard ERCP techniques (except perhaps for a reduced likelihood of pancreatitis), and is best employed by personnel who have extensive experience with therapeutic endoscopy. Technical details for a variety of clinical situations are described. Success requires application of 'the four Ps': position, practice, patience and perseverance.